A study of the drum language in Adzogbo - Locke, David L.; Agbeli, Godwin Kwasi (International Library of African Music, 1980)
The Eve-speaking people of the Guinea Coast of West Africa are rightly renowned for their highly developed drumming and dancing. Among the most exciting of their dances is Adzogbo, originally a warriors’ dance of the Fõ-speaking people of the ancient kingdom of Dahomey and now a recreational dance for the Fõ and Eve people of southern Benin, Togo and Ghana. Adzogbo is one of the most complex of the Eve dances, both in the intricacy of its polyrhythmic texture and the precise relationship of the rhythms of the master drum to the vigorous movements of the dancers. An outstanding feature of Adzogbo is the key role of drum language in the dance: every sequence of dance movements is introduced by a spoken or sung text which is then almost exactly reproduced in the rhythms of the master drum. Adzogbo thus provides excellent material for an analysis of drum language, especially the relationship between speech tone and drum strokes. In this article we shall sketch the general background of the dance and then look in detail at six examples of spoken texts and their associated drum rhythms.
Keywords: African Music